LC3/GABARAP family proteins: autophagy‐(un)related functions. Issue 12 (6th September 2016) - Schaaf, Marco B. E.; Keulers, Tom G.; Vooijs, Marc A.; Rouschop, Kasper M. A.
ABSTRACT: From yeast to mammals, autophagy is an important mechanism for sustaining cellular homeostasis through facilitating the degradation and recycling of aged and cytotoxic components. During autophagy, cargo is captured in double‐membraned vesicles, the autophagosomes, and degraded through lysosomal fusion. In yeast, autophagy initiation, cargo recognition, cargo engulfment, and vesicle closure is Atg8 dependent. In higher eukaryotes, Atg8 has evolved into the LC3/GABARAP protein family, consisting of 7 family proteins [LC3A(2 splice variants), LC3B, LC3C, GABARAP, GABARAPL1, and GABARAPL2]. LC3B, the most studied family protein, is associatedwith autophagosome development and maturation and is used tomonitor autophagic activity. Giventhe high homology, the other LC3/GABARAP family proteins are often presumed to fulfill similar functions. Nevertheless, substantial evidence shows that the LC3/GABARAP family proteins are unique in function and important in autophagy‐independent mechanisms. In this review, we discuss the current knowledge and functions of the LC3/GABARAP family proteins. We focus on processing of the individual family proteins and their role in autophagy initiation, cargo recognition, vesicle closure, and trafficking, a complex and tightly regulated process that requires selective presentation and recruitment of these family proteins. In addition, functions unrelated to autophagy of the LC3/GABARAP protein family members are discussed.—Schaaf, M. B. E., Keulers, T. G, Vooijs, M. A., Rouschop, K. M. A. LC3/GABARAP family proteins: autophagy‐(un)related functions. FASEB J. 30, 3961–3978 (2016). www.fasebj.org